Urban cultural vanguards why culture matters for urban success - Karima Kourtit; Peter Nijkamp (Journal of Urban Management, 2022)
This paper addresses the multifaceted relationships between culture and urban performance. It seeks to identify and examine evidence-based characteristics of urban success (or socio-economic performance) that are related to the cultural profile ("urban cultural value") of a city. Also, the broader socio-economic context and significance of "urban cultural magnets" is examined. The empirical analysis is based on a large international multivariate data base on the relevant characteristics of 40 global cities, and employs exploratory statistical analysis and regression models in a stepwise way. The analytical framework of our research is based on the overarching concept of an "urban cultural complex". The key cultural factors for urban performance are systematically assessed in a quantitative way. The study confirms the relevance of culture for the performance of contemporary large cities.
Keywords: 710; Cultural vanguards; Cultural performance; Urban century; Urban cultural complex